Jack Onyango on how the climate has changed in his community and ways they are dealing with it - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Jack Onyango is not only leading a youth group in Lower Kamula village, he is also a village elder. Wise for his age (35 years) he is leading his group to great yields and planning for a great future, trying to expand and improve farming in his community and among youths as the climate is changing. Learn more: www.ccafs.cgiar.org